Career adaptability and the success of self-initiated expatriates in China. Issue 4 (13th August 2019) - Jannesari, Milad; Sullivan, Sherry E.
Abstract : Purpose: Using a career lens, the purpose of this paper is to examine the psychological factors related to the career success (e.g. performance and adjustment) of self-initiated expatriates (SIEs). Design/methodology/approach: This research examines the previously unstudied relationship between career adaptability and career success. Data were collected by surveying 273 SIEs employed in professional jobs in China. Findings: As hypothesized, career adaptability was positively related to performance as well as to adjustment. Psychological availability mediated the relationships of career adaptability with performance and with adjustment. Contrary to expectations, supportive supervision did not moderate the relationship between career adaptability and either performance or adjustment. Research limitations/implications: Because the data were collected in a single, self-report survey, future studies should collect longitudinal data so that the effects of changes in career adaptability on adjustment and performance can be determined. In addition, as all of the participants were professionals, future research should examine SIEs employed in blue-collar jobs. Originality/value: As this is the first study to consider how career adaptability may influence SIEs' performance and adjustment, it offers unique insights into the work experiences of SIEs. Additionally, this study examines the theoretical underpinnings of career construction theory, namely, the previously hypothesized but untested relationship between career adaptability and adjustment.